1995
DOI: 10.2172/124999
|View full text |Cite
|
Sign up to set email alerts
|

Regional seismic discrimination research at LLNL

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Extensive research on regional earthquake event identification has shown that the spectral amplitude ratio of P-waves and S-waves, known as P/S ratio, is an effective method for distinguishing earthquakes from underground nuclear explosions [1][2][3] . Subsequently, the development of Magnitude and Distance Amplitude Correction (MADC) techniques has been used to refine the P/S discriminant [4][5][6] . The research on nuclear explosion identification provides various criteria that can potentially be used for distinguishing natural earthquakes from artificial blasting events.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research on regional earthquake event identification has shown that the spectral amplitude ratio of P-waves and S-waves, known as P/S ratio, is an effective method for distinguishing earthquakes from underground nuclear explosions [1][2][3] . Subsequently, the development of Magnitude and Distance Amplitude Correction (MADC) techniques has been used to refine the P/S discriminant [4][5][6] . The research on nuclear explosion identification provides various criteria that can potentially be used for distinguishing natural earthquakes from artificial blasting events.…”
Section: Introductionmentioning
confidence: 99%